Hepatic Epithelioid Hemangioendothelioma: A Case Report Emphasizing Diagnostic Challenges - Beyza Selvi; Ali Emre Bardak; Arzu Poyanlı; Bilger Çavuş (Annals of Internal Medicine: Clinical Cases, 2025)
Hepatic epithelioid hemangioendothelioma is a rare vascular tumor with variable clinical features, often leading to delayed diagnosis. We report a 40-year-old man presenting with abdominal distention and significant weight loss. Initial evaluations suggested cirrhosis and vascular pathologies, such as Budd–Chiari syndrome. Subsequently, liver biopsy confirmed hepatic epithelioid hemangioendothelioma. A positron emission tomography–computed tomography scan showed liver, bone, and possible colon involvement. Despite planning chemotherapy, the patient died before treatment initiation. This case highlights the importance of considering hepatic epithelioid hemangioendothelioma in the differential diagnosis of unexplained multifocal liver lesions, especially in middle-aged adults.